2006
DOI: 10.1111/j.1365-2141.2006.06243.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient self‐management of anticoagulation therapy: a trial‐based cost‐effectiveness analysis

Abstract: SummaryDemand for anticoagulation management is increasing due to an expansion of clinical indications for therapy. One possible model of care to meet demand is patient self-management (PSM), beneficial to patients who need control over their condition. This study aimed to determine the cost and cost-effectiveness of PSM of anticoagulation compared with routine clinicbased care for patients receiving long-term anticoagulation. A cost-utility analysis was conducted alongside a randomised controlled trial; 617 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 27 publications
1
54
0
Order By: Relevance
“…These findings were, however, sensitive to the unit costs applied to standard care monitoring visits. Applying the alternative standard monitoring unit costs estimated by Jowett and colleagues, 87 the opposite was observed, with self-monitoring dominating secondary care monitoring but being dominated by primary care monitoring.…”
Section: Assessment Of Cost-effectivenessmentioning
confidence: 97%
See 4 more Smart Citations
“…These findings were, however, sensitive to the unit costs applied to standard care monitoring visits. Applying the alternative standard monitoring unit costs estimated by Jowett and colleagues, 87 the opposite was observed, with self-monitoring dominating secondary care monitoring but being dominated by primary care monitoring.…”
Section: Assessment Of Cost-effectivenessmentioning
confidence: 97%
“…Contrary to this, several studies applied large effect estimates favouring self-monitoring in terms of TTR, thromboembolic events and/or mortality, and, subsequently, found self-monitoring strategies to be cost-saving or cost-effective. 33,86,88 In relation to the scope of this assessment, the two most relevant studies are those reported by Jowett and colleagues 87 and Connock and colleagues. 21 These economic evaluations were largely based on the same trial conducted in the UK.…”
Section: Summary Of Findings From Identified Studiesmentioning
confidence: 99%
See 3 more Smart Citations